Standardization of in vitro regeneration protocol in annual chrysanthemum - Pooja, A; Panwar, Sapna; Kumar, A.K; Kumar, Gunjeet (Indian Journal of Horticulture, 2022)
An efficient in vitro regeneration protocol of annual chrysanthemum (Chrysanthemum coronarium L.) was standardized by using leaf explants. Leaf segments (0.25 cm2) were taken from three weeks old in vitro raised plantlets and cultured on MS basal medium containing BAP, NAA and Kinetin at different concentrations. Maximum survival of micro shoots (86.67%) and shoot regeneration (82.79%) was achieved in half strength MS medium supplemented with BAP (0.5 mg/l) and NAA (1.0 mg/l) (T6). Half strength MS medium supplemented with GA3 (0.5 mg/l) (T3) showed thick shoots (5.78 cm) with dark green leaves and the highest rooting (90.00%) was recorded in the treatment including half strength MS basal medium supplemented with NAA (0.5 mg/l) (T3). The newly regenerated plantlets recorded maximum plant survival (76.60%) in medium containing cocopeat, perlite and vermiculite (1:1:1) (T2) supplemented with half strength MS inorganic broth. The study concluded that, the established protocol may be utilized in producing true to type plants which are otherwise difficult in the species. This protocol may help for large scale multiplication of desired types to fulfil the demand of quality planting material of C. coronarium.